Genetics and Genomics of Neurobehavioral Disorders - Fisch, Gene S; Ed (Humana Press, 2003)
Comprehensive and up-to-date, Genetics and Genomics of Neurobehavioral Disorders integrates the molecular, genomic, neuropsychological, and neurobehavioral factors that produce learning disabilities and mental retardation into a coherent framework for the understanding and assessment of neurobehavioral disorders."--Jacket.